Nádorové markery a jejich využití v klinické praxi - Machová, Iva; Brázdová, Andrea; Fusek, Martin; Zídková, Jarmila (Chemické listy, 2012)
Tumor markers known also as cancer or oncological markers are substances produced either by tumor or normal cells as a response to the presence of cancer . The markers are used for the detection, diagnosis, prognosis and control of treatment. There is no absolutely specific or universal cancer marker; therefore different markers for different cancer types are used in clinical practice. A problematic feature of cancer markers is their falsely positive results under physiological and non-cancer conditions.
Keywords: Clinical Medicine; klinické lékařství; prostatický specifický antigen; tkáňový polypeptidový antigen; nádorové biomarkery; alpha-Fetoproteins; Tissue Polypeptide Antigen; senzitivita a specificita; Sensitivity and Specificity; alfa-fetoproteiny; Biomarkers, Tumor; Prostate-Specific Antigen